2006
DOI: 10.1017/s0031182006000126
|View full text |Cite
|
Sign up to set email alerts
|

Robinia aurata n. g., n. sp. (Digenea: Hemiuridae) from the mugilid Liza aurata with a molecular confirmation of its position within the Hemiuroidea

Abstract: Robinia aurata n. g., n. sp. is described from Liza aurata (Mugilidae), the golden grey mullet, from the Ebro Delta, Spanish Mediterranean. The new genus differs from all other hemiurid genera in the combined possession of muscular flanges and a vestigial ecsoma. Within the Bunocotylinae, which currently accommodates 2 genera, Bunocotyle and Saturnius, the new genus exhibits a unique combination of blind caeca, Juel's organ, post-ovarian bulk of the uterus in the hind-body, and tegumental papillae surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 12 publications
6
32
0
Order By: Relevance
“…The relationships found within the superfamily Hemiuroidea, with two main clades separating the (Accacoelidae + Derogenidae + Syncoeliidae + Sclerodistomidae + Didymozoidae + Isoparorchiidae) and the (Hemiuridae + Lecithasteridae), are in agreement with previous studies (Blair et al 1998;Cribb et al 2003;Olson et al 2003;Pankov et al 2006). Nonetheless, our results differ slightly from those found by Blair et al (1998), since we found the Hemiuridae and Lecithasteridae to be polyphyletic, since more genetic data was included in the present analysis.…”
Section: Hemiurus Appendiculatus (Rudolphi 1802)supporting
confidence: 90%
See 2 more Smart Citations
“…The relationships found within the superfamily Hemiuroidea, with two main clades separating the (Accacoelidae + Derogenidae + Syncoeliidae + Sclerodistomidae + Didymozoidae + Isoparorchiidae) and the (Hemiuridae + Lecithasteridae), are in agreement with previous studies (Blair et al 1998;Cribb et al 2003;Olson et al 2003;Pankov et al 2006). Nonetheless, our results differ slightly from those found by Blair et al (1998), since we found the Hemiuridae and Lecithasteridae to be polyphyletic, since more genetic data was included in the present analysis.…”
Section: Hemiurus Appendiculatus (Rudolphi 1802)supporting
confidence: 90%
“…Nonetheless, our results differ slightly from those found by Blair et al (1998), since we found the Hemiuridae and Lecithasteridae to be polyphyletic, since more genetic data was included in the present analysis. The combined analysis of both ribosomal regions showed a topology very similar to that obtained by Pankov et al (2006), but in our analysis, the basal topology of the clade that includes the families Hemiuridae and Lecithasteridae was better resolved. The lecithasterid Machidatrema chilostoma, the hemiurid Opisthadena dimidia and the monophyletic hemiurid subfamily Bunocotylinae constitute a consistent clade that is basal in the hemiurid/lecithasterid clade.…”
Section: Hemiurus Appendiculatus (Rudolphi 1802)supporting
confidence: 76%
See 1 more Smart Citation
“…Aponurus sp. of Pankov et al (2006) Type-host: Mullus barbatus L. Other host: Mullus surmuletus L. Type-locality: Off Besòs, Spain. (Pankov et al, 2006) and HQ713441 (present study).…”
Section: Methodsmentioning
confidence: 99%
“…L. aurata and L. saliens are new host records for S. minutus. Pankov et al (2006) described Robinia aurata Pankov, Webster, Blasco-Costa, Gibson, Littlewood, Balbuena & Kostadinova, 2006 from Liza aurata (Mugilidae) from the Spanish Mediterranean. These authors developed a phylogenetic hypothesis for the Bunocotylinae from sequence data analyses based on partial lsrDNA and complete ssrDNA combined (22 species) and V4 domain of the ssrRNA gene (37 species).…”
Section: Remarksmentioning
confidence: 99%